The Look : ethics and ontology in Herman Melville's The Piazza, Bartleby, the Scrivener, and Benito Cereno - Bigagli, Francesca (Trinity College (Dublin, Ireland). School of English, 2003)
This thesis proposes to answer to the question of the Other and the Other as question in Herman Melville's The Piazza (January and February 1856), Bartleby, the Scrivener; a Story of Wall Street (November and December 1853) and Benito Cereno (October, November and December 1855).
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin